Pembuatan Digital Terrain Model (DTM) dari Light Detection and Ranging (LiDAR) menggunakan Metode Morfologi Sederhana - Safi'i, Ayu Nur; Hartanto, Prayudha (TEKNIK, 2019)
The production of Indonesian Topographic Map (RBI) in the scale of 1:5000 takes a long time, especially in the making of contour layer. Contour layer can be extracted from both Aerial Photogrammetry and LiDAR data. Nowadays, LiDAR technology is getting more reliable for DSM. From DSM can be exctracted to get DTM/DEM. DTM/ DEM generation because of its shorter processing  time  and  relatively  low  cost.  The  filtering  method  used  in  this  research  is  Simple Morphological Filtering (SMRF) which input parameters are: cell size, slope, windows, elevation threshold and scaling factor. Average value of Cohen’s kappa is in the range of 0.4-07 which means that the generated DTM is good. Because of the existence of null values in the generated DTM, the smoothing filters have been applied. The extracted DTM then be compared to in situ data. The RMSE ranged from 0,621 to 0,930 m and LE90 about 1,025-1,605. Those RMSE and LE90 values satisfied the vertical accuracy of the 1: 5000 topographic map and graded as the second and third class in accordance to BIG Regulation No.6 of 2018 as revision of Perka BIG No.15 of 2014 focusing on Technical guidelines for Basic Map Accuracy.